The political participation of the Roma in Slovenia - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The article deals with the system of political participation of the Roma in Slovenia, focusing on the municipal level. It contains an analysis of the development of the legal regulation of political representation of the Roma and the system of electing Roma municipal councillors. There is discussion of problems connected with the establishment of the institute of Roma municipal councillors, resulting mainly from unclear and inadequate legislation. The article further discusses the role and importance of the Roma Community Council as the umbrella Roma organisation in Slovenia. The introduction of the institute of Roma municipal councillors is seen as an important step forward in the political inclusion of the Roma, while the current form and way of working of the Roma Community Council are not believed to offer the right foundations for the development of legitimate and effective Roma representation at the national level.
Keywords: Slovenia; Slovenija; politična participacija; politično predstavništvo; občine; Romi; zakonodaja; Svet romske skupnosti; romski občinski svetniki